INVESTIGATING NETWORK THREATS TO ENSURE MAXIMUM PROTECTION OF DATA AND INFRASTRUCTURE - KUSHNIR, YURII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
It was shown the need of augmenting of quantity of produced foodstuffs in view of systematic increasing of global population, what is especially necessary for developing countries. At the same time the sizeable quantity of men have excessive weight because of excessive caloricity of ration. In this reason, the UN Food and Agricultural Organization calculated the optimized need of adults in albumens, fats and hydrocarbons. It was shown that the biggest income of energy in energy necessary for keeping of metabolism of men in order put fats and hydrocarbons, and the energetic quota of albumens in this balance is of minor value for their principal role consists in satisfying of plastic needs of the organism. That’s why ones who plan ration of men, especially in including in it of innovative products, has to look first for the need of decreasing of caloricity of the basic ration, and accent on putting in it augmented quantities of albumens. At the same time, developers of the product have to keep in mind the meet-producing industry is character by huge negative influence of ecological state of the Planet and influences greatly on process of its global warming. This was the principal reason of development of the milled semi-finished product based on use of vegetative raw materials instead of meat-based analogues. Taking this reason in mind, we choose as the principal source of albumens in the mix the soy and wheat texturate, which contains up to 70 % of this component in the mass. There was studied the chemical composition of the product in development, which principal ingredients are the soy and wheat texturate (21.0 %), coconut oil (6.3 %), and sunflower oil (5.0 %), and shown that such mix contains 11.82 % of albumens, what is considerable more of quantity of albumens in the mix regulated by national standard of ДСТУ 4823.2:2007 beef of 7.41 % in the beef-based mix. At the same time the product in development is character by considerably lesser caloricity of 744 kJ per 100 grams of the mix as compared with the same index of the meat-based mix of 1320 kJ per 100 grams. Taking the found advantages of the innovative product in mind, there was developed the basic diagram of its manufacturing, and detailed the main operation of its producing including the stages of preparation of water-and-fat emulsion, hydration of soy and wheat texturate, and preparing of minced mix. It was shown earlier as well the complex of positive properties of the innovative product.